NURSING STUDENT’S LIFESTYLE IN THE AREAS OF BEHAVIORAL WHEEL: Received: 31st December 2020; Revised: 13th March 2021, 09th June 2021; Accepted: 13th June 2021 - Lacsa, Janet E; De Jesus, Lady Anne O; Martinez, Ma. Cecilia O (LIFE: International Journal of Health and Life-Sciences, 2021)
This study was conducted to determine the nursing student’s lifestyle in the areas of the behavioral wheel (Mental Health, Family and Social Health, Nutritional Health, Physical Fitness / Health, Disease and Disorder, Control of Substance Abuse, Growth and Development, Safety and First Aid, Consumer and Personal Health, Community and Environmental Health) using an adopted and modified survey-questionnaire. Results showed that: most of the nursing students were level 1, female, with average income, and good academic standing; they have a very high manifestation of healthy lifestyles in the areas of Family and Social Health, Control of Substance Abuse, and Consumer and Personal Health; high manifestation of healthy lifestyles in the areas Mental Health, Growth and development, Safety and First Aid, Community and Environmental Health, and Disease and Disorder; moderate manifestation of healthy lifestyles in the areas: Nutritional health and Physical Health. Results also showed that the nursing students have significant differences in their manifestation of healthy lifestyles for areas Growth and Development, Nutritional Health, Safety, and First Aid, and Community and Environmental Health when they were grouped according to gender; have significant differences in their manifestation of healthy lifestyles for all areas of the behavioral wheel when grouped according to economic status - income; have significant differences in their manifestation of healthy lifestyles for areas Mental Health, Nutritional Health, Disease and Disorders, and Safety and First Aid when grouped according to year level; and lastly have significant differences in their manifestation of healthy lifestyles for areas in the areas: Mental Health, Nutritional Health, Safety, and First Aid, and Disease and Disorders when grouped according to academic standing.